Description of a novel cyanobacterial species Elainella ringii sp. nov. (Oculatellales) from Himalayan hot spring, Uttarakhand, India using polyphasic approach - Bhandari, Munni; Sonam, Sonam; Negi, Rahul; Singh, Preeti; Singh, Rahul Kunwar; Dadheech, Pawan K. (Phytotaxa, 2025)
Cyanobacteria are oxygenic photosynthetic prokaryotes capable of surviving in harsh environments ranging from semi-arid to arid regions, hot springs and polar regions. Exploration of cyanobacterial diversity from such habitat is taxing due to variable temperature, fluctuating pH, and unique chemical compositions, though it harbours various unexplored taxa that calls for divulgence. Therefore, the present investigation aimed to characterize a filamentous cyanobacterium isolated from a mat growing in Ringi hot spring located in Tapovan, Uttarakhand, India, using polyphasic approach. Morphological analysis revealed that the studied strain exhibited Leptolyngbya-like morphology with the characteristic features such as straight filaments, non-heterocytous cells with less than 3.5 µm width. The optimum temperature for the growth of isolated strain was 30°C. However, molecular and phylogenetic analysis based on 16S rRNA gene, evinced that the studied strain is closely related to genus Elainella rather than Leptolyngbya. The phylogenetic tree constructed using maximum-likelihood (ML) and Bayesian inference (BI) method shows that the studied strain forms a distinct lineage with high standard bootstrap/ultrafast bootstrap/posterior probability values (91%/100%/1) that were consistent with the p-distance similarity matrix. Additionally, analysis of the D1-D1’ helix, BoxB helix, and V3 region of the 16S-23S ITS gene indicates significant differences from related taxa, reinforcing the taxonomic status of the studied strain. Henceforth, on the basis of morphological, physiological, molecular, phylogenetic and ecological characteristics, we provide the description of new taxon: Elainella ringii sp. nov.